The Metaphor of Slavery in Heart of Darkness and La Voragine: Common Ground between Joseph Conrad and Eustasio Rivera - Somale, Marisel Adriana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2014)
A comparative study of a prestigious figure of speech is carried out –that of the metaphor- and research is done on the strange unfolding of quest, awareness and descent into the human condition accomplished by both Joseph Conrad in “Heart of Darkness” and Eustasio Rivera in “The Vortex” in the complexity of two voyages that take place in the diversity of the exotic jungle, although analogous, in its natives, and in its unexpected strange fascination.